UTILIZATION OF VIDEOMOTION ANALYSIS FOR ASSESSMENT OF BALANCE IN THE PATIENTS WITH PARKINSON'S DISEASE - S. A. Likhachev; V. V. Vashchylin; V. V. Goursky (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The objective of the research was to develop a method for the assessment of balance impairment in Parkinson's disease, based on videomotion analysis. The developed method for the assessment of balance function in the patients with Parkinson's disease does not require expensive equipment, and may be utilized while pre- and postoperative examination of patients with Parkinson's disease.